2014
DOI: 10.2147/dddt.s57258
|View full text |Cite
|
Sign up to set email alerts
|

Update on the clinical utility and practical use of ropivacaine in Chinese patients

et al.

Abstract: We reviewed the Chinese and English literature for efficacy and tolerability data as well as pharmacological properties of ropivacaine in Chinese patients. Ropivacaine is a long-acting amide local anesthetic agent that elicits nerve block via reversible inhibition of sodium ion influx in nerve fibers. The available evidence in the literature on anesthesia practice indicates that ropivacaine produces equally surgical sensory block and postoperative and obstetrics analgesia with good maternal and fetal outcome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 80 publications
3
10
0
Order By: Relevance
“…In this investigation, we performed the OSTAP block before general anesthesia induction and endotracheal intubation. Our results showed that several intraoperative parameters in group T, including sufentanil dosage, the number of patients who used a vasodilator and the time to extubation, were significantly less than those in group C. Compared with group C, cumulative sufentanil consumption till postoperative24h and NRS pain scores at 2 h and 4 h postopertively decreased significantly in group T. Our results were consistent with previous findings where TAP blocks have been described to last from 6 h to 24 h using ropivacaine [ 7 , 16 , 22 24 ]. The duration of the peripheral nerve block depends on several factors, such as the choice of local anesthetics, the site of injection and the presence of adjuncts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this investigation, we performed the OSTAP block before general anesthesia induction and endotracheal intubation. Our results showed that several intraoperative parameters in group T, including sufentanil dosage, the number of patients who used a vasodilator and the time to extubation, were significantly less than those in group C. Compared with group C, cumulative sufentanil consumption till postoperative24h and NRS pain scores at 2 h and 4 h postopertively decreased significantly in group T. Our results were consistent with previous findings where TAP blocks have been described to last from 6 h to 24 h using ropivacaine [ 7 , 16 , 22 24 ]. The duration of the peripheral nerve block depends on several factors, such as the choice of local anesthetics, the site of injection and the presence of adjuncts.…”
Section: Discussionsupporting
confidence: 90%
“…The duration of the peripheral nerve block depends on several factors, such as the choice of local anesthetics, the site of injection and the presence of adjuncts. Ropivacaine is the most frequently used local anesthetic for peripheral nerve block in the People’s Republic of China [ 22 ]. Lee et al [ 16 ] demonstrated that maximal dermatome spread was observed at 30 min and usually regressed by 24 h. Although few studies have shown the analgesic effect lasting longer than 24 h [ 25 ], Stoving et al [ 24 ] demonstrated that the blockade duration of ultrasound-guided unilateral TAP block with 20 mL 75 mg/mL ropivacaine was approximately 10 h with a large variation in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses confirm that a local anesthetic injection reduces postoperative pain for pediatric tonsillectomies on PODs 0 and 1, consistent with a prior meta‐analysis with 7 studies utilizing topical or locally injected anesthetics 3 . Bupivacaine (with or without epinephrine), levobupivacaine (with or without epinephrine), lidocaine with epinephrine, and ropivacaine all have a duration of action of 3 to 6 hours, making them easier to compare than other anesthetics 16–18 . Interestingly, subgroup analysis on pain scores reported in the 4‐ to 8‐hour time frame identified a significant difference favoring local anesthetic in 2 groups: cold technique only and cold technique with electrocautery.…”
Section: Discussionsupporting
confidence: 76%
“…observed in rats with this ophthalmic formulation of oxybuprocaine, which agrees with these aforementioned studies [5,9,11]. The clinical use of ropivacaine hydrochloride has increased in human anesthesia and analgesia practice in recent years [25]. While, several studies have addressed the clinical utility of ropivacaine hydrochloride in human and veterinary ophthalmology [26][27][28][29][30].…”
Section: Plos Onesupporting
confidence: 81%
“…The clinical use of ropivacaine hydrochloride has increased in human anesthesia and analgesia practice in recent years [ 25 ]. While, several studies have addressed the clinical utility of ropivacaine hydrochloride in human and veterinary ophthalmology [ 26 – 30 ].…”
Section: Discussionmentioning
confidence: 99%